LEADERSHIP IMPACT ON ACCOUNTANTS’ COMPETENCE AND AI ADOPTION READINESS - William Octandy Tamara; Yonathan Christian Azarya Fulbertus; Hendri Kwistianus (Jurnal Akuntansi Kontemporer, 2026)
Research Purposes. This study aims to explore how leadership affects employee competence and organizational readiness to adopt AI in Indonesian firms from the perspective of accountants. Research Methods. This research collected data through purposive sampling. The model was tested using PLS-SEM methodology from 280+ professional accountants in Indonesia, facilitated by SmartPLS. The result revealed that leadership has a significant influence on affecting Employee Competence, Organizational Readiness and AI Adoption. In addition, Organizational Readiness and Employee Competence have a significant impact on AI Adoption and significantly mediate the Leadership-AI Adoption relationship. Research Results and Findings. This study is among the few in Indonesia to empirically validate Employee Competence (EC) and Organizational Readiness (OR) as mediators of the relationship between Leadership and AI Adoption. This offers a refined perspective on how Leadership, Employee Competence, and Organizational Readiness drive AI integration in Indonesia’s context. The study's findings are beneficial to organizations, providing more in-depth information on the roles of Leadership, Employee Competence, and Organizational Readiness in adopting AI. Especially for companies that are planning to use AI in the future, or are currently integrating AI in their business process.